PHYSICO-CHEMICAL PROPERTIES OF CONTROLLED HYDROPHILIC-HYDROPHOBIC SILICA. - Muyassarova Ryan Ikram's Qizi; Karayev Sarvar Egamnazar ugli; Kattayev Nuritdin Toraevich; Akbarov Hamdam Ikramovich (Scholar Express Journal, 2023)
This paper examines the physico-chemical properties of a controlled hydrophilic-hydrophobic silicon in light of the surface change technique and their effects on the material's properties. The study includes a full analysis of the literature, experimental methods, results, and discussions to ensure comprehensive understanding of the subject.
Keywords: Controllable silica; hydrophilic-hydrophobic modification; physicochemical properties